Implementasi Peraturan Daerah Kabupaten Sikka Nomor 11 Tahun 2012 Tentang Pengawasan dan Pengendalian Minuman Beralkohol - George Frederik Yulio Jano; Rafael Rape Tupen; Hernimus Ratu Udju (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
Drinking and uncommendable behavior are two intertwined things. Recently, an event that has disturbed the community has become more frequent. Some sexual crimes against children occur after the perpetrator drinks alcohol, where people will be encouraged to commit heinous acts, when their intellect has been influenced by alcohol. The Sikka Regency Government together with the Sikka Regency Regional People's Representative Council made Sikka Regency Regional Regulation Number 11 of 2012 concerning the Supervision and Control of Alcoholic Beverages, as a preventive effort to overcome social problems in the community, namely, the high number of traffic accidents, Domestic Violence (KDRT) and vandalism triggered by alcoholic beverages. This research is an empirical juridical law research. This study is descriptive and analyzes primary data to find out the Implementation of Sikka Regency Regional Regulation Number 11 of 2012 concerning Supervision and Control of Alcoholic Beverages. Data collection uses observation, documentation and interview techniques. The results of the study show that: (1) The implementation of Sikka Regency Regional Regulation Number 11 of 2012 concerning Supervision and Control of Alcoholic Beverages needs to be followed up because there are still obstacles faced (2) The impact of the Implementation of Sikka Regency Regional Regulation Number 11 of 2012 concerning Supervision and Control of Alcoholic Beverages, one of which is a decrease in revenue.